The Influence of Green Influencer towards Purchase Intention: The Extended Theory of Planned Behavior Approach - Prayogo, Guntur; Adiwijaya , Karto (Yayasan Sinergi Kawula Muda, 2025)
Social media users have grown significantly, reaching 60% of the Indonesian population. Among those users is Pandawara Group, a green social media influencer known for its environmental activism on social media platforms such as TikTok and Instagram. Pandawara Group gained popularity in a short period of time due to its unique content and currently has 10 million active followers, making Pandawara Group a Mega Influencer in less than a year. This research examines the role of the Pandawara Group in promoting green purchase intention through the lens of the Theory of Planned Behavior (TPB). The study focuses on and employs a quantitative approach, utilizing surveys distributed to followers of the Pandawara Group with 122 samples collected. Then, the data is processed through SEM-PLS with the help of SmartPLS. The findings indicate that perceived credibility and expertise attributes positively affect attitudes toward green behavior. The study also finds that perceived congruence positively and significantly influences parasocial relationships, which in turn significantly influences green purchase intentions.